PERSEPSI MASYARAKAT TERHADAP PENGGUNAAN DOMPET DIGITAL PADA TRANSAKSI JUAL BELI - Jasri, Jasri; Indah Rahayu; Andi Muhammad Aidil; Sitti Hajerah (MANAJEMEN, 2021)
Current technological developments can no longer be denied, various innovations are continuously present to pamper consumers in the transactions they make. The innovations that are present include a payment system that can already be done through a digital system called a digital wallet. The presence of these various digital wallet platforms must compete very tightly to win the hearts of consumers. To win the hearts of consumers, of course, you have to know what the needs and expectations of consumers are for these new innovations. The purpose of this study is to find out what are the public perceptions of using digital wallets in digital transactions. The method used in this research is quantitative research with a descriptive approach. The results of the study show that people have a tendency to use a digital wallet platform for the reason of getting more convenience and security in transactions they make with digital wallets compared to transactions with other systems.